2019
DOI: 10.1097/cm9.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum vitamin D, adipose tissue vitamin D receptor, and peroxisome proliferator-activated receptor γ in women with gestational diabetes mellitus

Abstract: Background:Gestational diabetes mellitus (GDM) is a common complication during pregnancy. Obesity and overweight are closely related to metabolic diseases and diabetes. However, the role of adipose tissue in the pathogenesis of GDM remains to be studied. The aim of this study was to investigate the correlation of vitamin D (VD) levels, VD receptor (VDR), and peroxisome proliferator-activated receptor γ (PPARγ) expression with GDM in overweight or obese women.Methods:One hundred and forty pregnant women with fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…No additional research has been reported on the role of the Thr397 phosphorylation since its first publication in 2015. There is a general consensus in citing literature that Cdk5 is the sole kinase responsible for phosphorylating Ser273 of PPARγ ( 44 , 45 , 46 , 61 , 67 , 68 , 69 ). Recent publications acknowledged the activities of ERK as the kinase of interest ( 57 , 70 , 71 ) or cited a combination of the two kinases ( 37 , 72 , 73 , 74 ).…”
Section: Kinase Ambiguity Has Been Hampering Pser273-directed Researchmentioning
confidence: 99%
“…No additional research has been reported on the role of the Thr397 phosphorylation since its first publication in 2015. There is a general consensus in citing literature that Cdk5 is the sole kinase responsible for phosphorylating Ser273 of PPARγ ( 44 , 45 , 46 , 61 , 67 , 68 , 69 ). Recent publications acknowledged the activities of ERK as the kinase of interest ( 57 , 70 , 71 ) or cited a combination of the two kinases ( 37 , 72 , 73 , 74 ).…”
Section: Kinase Ambiguity Has Been Hampering Pser273-directed Researchmentioning
confidence: 99%
“…[203][204][205][206] VD binds the vitamin D receptor (VDR) for signal transduction and interacts with other factors, such as the vitamin D-binding protein, retinoid X receptor, and peroxisome proliferator-activated receptor (PPAR). 170,171,207,208 Previous studies have shown that the Th-2 cell response plays an important role in the pathogenesis of T1DM and AITD, [209][210][211][212] whereas VD supplementation reverses the inappropriate activation of T cells and improves immune homeostasis, suggesting a therapeutic value for VD in concurrent autoimmune diseases. 145,189,211 VDR is critical for the correct biological function of VD in several processes such as the modulation of calcium homeostasis and bone growth.…”
Section: Infectious Factorsmentioning
confidence: 99%
“…A Chinese study by Wang et al in 2019 concluded that VD3 may play a role in the manifestation of GDM by controlling the development of adipocytes through VD3 receptors and peroxisome proliferator-activated receptor γ (PPARγ) pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%